CARBON IN SOIL IN DIFFERENT PHISIONOMIES OF CAATINGA IN PARAÍBA, BRAZIL - Souza, Bruna Vieira de; Souto, Patrícia Carneiro; Souto, Jacob Silva; Sales, Francisco das Chagas Vieira; Souza Junior, Carlos Magno Pereira de (Floresta, 2019)
The devastation of the caatinga vegetation by disorderly exploration has led to the intensification of carbon release, modifying the capacity of soils to stock this element. The study aimed to determine the stock of organic carbon in Caatinga areas. Which it was conducted in the city of Várzea, state of Paraíba in Brazil, in four areas with vegetation in different successional stages. Soil samples were collected to determine the levels of carbon in 04 depths (0-5 cm, 5-10 cm, 10-15 cm and 15-20 cm) in two seasons of the year. The averages of the carbon were compared by Tukey test. The amounts of carbon in the soil showed significant differences in the factors of time, study area and depth. In the dry season, the quantities and the carbon stock were higher than those registered in the rainy season in all the studied areas, being Late Secondary Caatinga and Preserved Caatinga the areas with the highest values. The Late Secondary Caatinga had the highest carbon stock (33.01 Mg ha-1) in the rainy season. On the other hand, in the dry season, the highest carbon stock was in Preserved Caatinga (49.77 Mg ha-1). Larger amounts of organic carbon were found in the area of Preserved Caatinga, being the higher carbon concentrations recorded in the dry season.